Transformasi Komunikasi Pendidikan di Era Digital - Abigail Brenda Tinambunan; Lunayla Putri Bintari; Satia Adeliana; Salma Mulia Afas; Pinky Julia Ningsih Nainggolan; Najla Faadiyah; Ere Mardella Arbiani (YAYASAN PADHANG MANAH SIBYAN, 2026)
The digital era has brought about fundamental changes in various aspects of life, including education. Educational communication, as a crucial element in the teaching and learning process, is undergoing a significant transformation due to advancements in information and communication technology. This scientific article aims to conceptually explore the transformation of educational communication in the digital era. The discussion includes the evolution of communication from traditional face-to-face to the virtual realm, the central role of technologies such as the internet, digital media, online platforms, and smartphones, and their impact on teacher-student interactions. Furthermore, this article examines the benefits offered, such as accelerated access to information, learning flexibility, and creativity stimulation, as well as the challenges faced, including a lack of direct interaction, concentration disturbances, and access disparities. Strategies to enhance the effectiveness of digital educational communication are also proposed, emphasizing the wise use of technology, the utilization of interactive media, and the synergistic role of educators and parents. Relevant educational communication theories from scholars like McLuhan, Moore, Rogers, Vygotsky, Dale, and Bruner are integrated to provide a strong theoretical foundation. This article references over 25 leading scientific sources to support its analysis.